2017
DOI: 10.1155/2017/6941306
|View full text |Cite
|
Sign up to set email alerts
|

A Multiorgan Segmentation Model for CT Volumes via Full Convolution-Deconvolution Network

Abstract: We propose a model with two-stage process for abdominal segmentation on CT volumes. First, in order to capture the details of organs, a full convolution-deconvolution network (FCN-DecNet) is constructed with multiple new unpooling, deconvolutional, and fusion layers. Then, we optimize the coarse segmentation results of FCN-DecNet by multiscale weights probabilistic atlas (MS-PA), which uses spatial and intensity characteristic of atlases. Our coarse-fine model takes advantage of intersubject variability, spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In the network structure, there are only convolution layer and pooling layer. There is no full connection layer [12,13]. The difference of the two network structures is that up-sampling and down-sampling in U-Net network adopt the same level of convolution operation.…”
Section: U-net Networkmentioning
confidence: 99%
“…In the network structure, there are only convolution layer and pooling layer. There is no full connection layer [12,13]. The difference of the two network structures is that up-sampling and down-sampling in U-Net network adopt the same level of convolution operation.…”
Section: U-net Networkmentioning
confidence: 99%
“…Quite a few studies reported multiorgan segmentation with duodenum organ which plays crucial role in video-endoscopy. Thus, satisfactory research work is required for clinical acceptance for small organs especially pancreas and duodenum [2].…”
Section: A Organ Selectionmentioning
confidence: 99%
“…But it is impractical solution to have radiologists for manual individual organ detection and it consumes more resources such as time, material and labor. That's why lots of work has been conducted to automate organ segmentation systems [2]. Although huge amount of research is carried out for single organ segmentation [3]- [8] but more attention is yet to be required for multiorgan segmentation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations